2021
DOI: 10.1051/0004-6361/202141886
|View full text |Cite
|
Sign up to set email alerts
|

Long-term multi-band photometric monitoring of Mrk 501

Abstract: Aims. Radio-to-TeV observations of the bright nearby (z = 0.034) blazar Markarian 501 (Mrk 501), performed from December 2012 to April 2018, are used to study the emission mechanisms in its relativistic jet. Methods. We examined the multi-wavelength variability and the correlations of the light curves obtained by eight different instruments, including the First G-APD Cherenkov Telescope (FACT), observing Mrk 501 in very high-energy (VHE) gamma-rays at TeV energies. We identified individual TeV and X-ray flares… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…For Mrk 501, the data from Swift-UVOT in the UVW2 band were taken from Arbet-Engels et al (2021), covering a noncontinuous period between 2015 June and 2018 April. From optical to radio, the data are taken from Abdo et al (2011b).…”
Section: Uv Optical and Radio Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For Mrk 501, the data from Swift-UVOT in the UVW2 band were taken from Arbet-Engels et al (2021), covering a noncontinuous period between 2015 June and 2018 April. From optical to radio, the data are taken from Abdo et al (2011b).…”
Section: Uv Optical and Radio Datamentioning
confidence: 99%
“…A few years later, in 2009, the Fermi collaboration organized a multiwavelength campaign to study the Mrk 501 SED, which was built with data from radio to gamma-rays; the MAGIC telescope participated with 16.2 hr of observation and the VERITAS array telescopes with 9.7 hr, of which 2.4 hr were during a high-activity state of the source; an SSC model was fit to the data, showing that relativistic proton shock waves are related to the bulk of the energy dissipation within the source emission zone (Abdo et al 2011b). Also, between 2012 December and 2018 April, FACT monitored Mrk 501 at TeV energies for a total of 1344 hr, distributed over 633 nights (Arbet-Engels et al 2021).…”
Section: Introductionmentioning
confidence: 98%
“…The correlation between the GeV and radio light curves is also strong in Mrk 501 with radio variations lagging behind the GeV ones by 170−250 days (Arbet-Engels et al 2021b). To further probe the connection between these bands, we searched for the delayed response profile, which, when convolved with the GeV light curve, can mimic the radio variations.…”
Section: Mrk 501mentioning
confidence: 94%
“…Using a 5.5 year data set from Mrk 501, from 2012 to 2018, the FACT collaboration (Arbet-Engels et al 2021) has recently shown a positive correlation between the Fermi-LAT fluxes and those from OVRO, with a relatively flat behaviour and with time lags extending from -300 days to +300 days; the significance of such correlated behaviour was not computed (see Fig. 9 of Arbet-Engels et al 2021). In our study, that employs a 12-year data set, we show that the correlation is statistically significant (> 3σ) only for time lags larger than -100 days, implying the radio emission is connected to the γ-rays with a delay larger than 3 months.…”
Section: Multi-band Variability and Correlationsmentioning
confidence: 99%
“…As summarized in , Mrk 501 was regularly observed by the first generation of VHE instruments (HEGRA, Whipple, CAT) from 1996 to 2000 as shown by the light curve (LC) in Fig. A.1. Subsequently, the new generation of imaging atmospheric Cherenkov telescopes (IACTs), MAGIC, H.E.S.S., VERITAS and FACT, have been observing the source since 2005 together with regular observations in other wavebands Anderhub et al 2009;Aleksić et al 2015a;Acciari et al 2011;Aliu, E. et al 2016;Abdo et al 2011a;Ahnen et al 2017aAhnen et al , 2018Furniss et al 2015;Acciari et al 2020a;Cologna et al 2017;Arbet-Engels et al 2021). A coarse overview of the broadband emission of Mrk 501 from the year 2005 to the year 2020 is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%